2017
DOI: 10.16965/ijar.2017.364
|View full text |Cite
|
Sign up to set email alerts
|

Study of Variations in the Branching Pattern and Distance of Origin of Branches of Posterior Cord of Brachial Plexus

Abstract: Background: Keeping in mind the frequency at which the surgical procedures are performed in the axilla, the organization and branching of brachial plexus and its topography becomes clinically significant and it is extremely complicated. Brachial plexus is the seat of explorations for oncosurgeons operating for breast carcinoma, schwannoma, neurofibroma, Anesthesiologists performing brachial plexus block, Plastic surgeons harboring myo-cutaneous flaps, Orthopedicians dealing with shoulder arthroplasty, humeral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Our study showed that one of the most important anatomical landmarks was the azygos venous arch. At the same time, its vertebral level is subject to variation from the T2 level to the T5 level [13,20,24,30]. According to our data, its most frequent location is at the T4 level (56.7%), which is consistent with the other authors' data (52.8%) [20], and slightly different from the data of the investigators, who showed that this level corresponds more frequently to the T5 level [24].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our study showed that one of the most important anatomical landmarks was the azygos venous arch. At the same time, its vertebral level is subject to variation from the T2 level to the T5 level [13,20,24,30]. According to our data, its most frequent location is at the T4 level (56.7%), which is consistent with the other authors' data (52.8%) [20], and slightly different from the data of the investigators, who showed that this level corresponds more frequently to the T5 level [24].…”
Section: Discussionsupporting
confidence: 70%
“…At the same time, its vertebral level is subject to variation from the T2 level to the T5 level [13,20,24,30]. According to our data, its most frequent location is at the T4 level (56.7%), which is consistent with the other authors' data (52.8%) [20], and slightly different from the data of the investigators, who showed that this level corresponds more frequently to the T5 level [24]. Furthermore, it has been demonstrated that the azygos vein joins the superior vena cava at the T3 level in 62.5% [13] and 53.33% [18], while the arch of the azygos vein and its confluence with the superior vena cava were at the same level [20].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] and is summarized in Table 2. The highest incidence was reported by Rastogi 6 (22.9%) and the lowest by Darji 4 (1%).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of origin of axillary nerve as a common trunk from the posterior cord of brachial plexus varies from 1%-22.9% in various studies. [7][8][9][10][11] and is summarized in Table 2. The highest incidence was reported by Rastogi [8] (22.9%) and the lowest by Darji [10] (1%).…”
Section: Discussionmentioning
confidence: 99%
“…Author Number of specimens Origin from posterior cord Origin as a common trunk from posterior cord Chaudhary P et al 2011 [7] 60 96.67% 3.33% Rastogi R et al 2012 [8] 74 77.10% 22.90% Gaur S et al 2012 [9] 50 92% 8% Darji A et al 2013 [10] 100 99% 1% Bhosale SM et al 2014 [11] 40 87.50% 12.50%…”
Section: Fig 2 Showing Branches Of Axillary Nervementioning
confidence: 99%